2021 IEEE International Conference on Artificial Intelligence and Virtual Reality (AIVR) 2021
DOI: 10.1109/aivr52153.2021.00061
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor learning in immersive virtual reality: a scoping literature review

Abstract: The benefits and drawbacks of using immersive virtual reality (IVR) for learning are increasingly being explored, with growing evidence that a major contributor to IVR learning benefits are the sensorimotor-based affordances of the technology. However, to our knowledge, there have been no reviews of sensorimotor-based IVR learning studies for academic or cognitive learning. In order to provide an overview of the field, we present a scoping review based on a comprehensive search that identified 14 documents rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…ese studies reviewed the previous articles to answer specific research questions for understanding important keywords or topics of the field. Some review papers focused on the trends of virtual reality-based education research related to specific fields as shown in Table 1, such as Earth science engineering education [7], medical education [8,19], STEM education [20], math education [21], computer science education [22], higher education [23][24][25], heritage education [26], rehabilitation management of breast cancer survivors [27], virtual reality-based training for daily living in patients with chronic stroke [28], PSTD treatments [29], foreign language learning gamification using virtual reality [30,31], K-12 and higher education [15,17], surgical training [32], industrial skills training [31], virtual reality cognitive training in individuals with mild cognitive impairment [16,18], science education [33,34], sensorimotor learning [35], dental education [36], virtual reality-based emotional response and symptom provocation in patients with OCD (obsessive compulsive disorder) [37], nursing education [38,39], virtual reality therapy for social anxiety disorder [40], evacuation training [41], virtual reality-assisted neuromuscular therapy [42], home-based virtual reality rehabilitation for individuals with Parkinson disease [43], virtual realitybased physiology and anatomy learning [44], social work education [45], and marketing higher education …”
Section: Introductionmentioning
confidence: 99%
“…ese studies reviewed the previous articles to answer specific research questions for understanding important keywords or topics of the field. Some review papers focused on the trends of virtual reality-based education research related to specific fields as shown in Table 1, such as Earth science engineering education [7], medical education [8,19], STEM education [20], math education [21], computer science education [22], higher education [23][24][25], heritage education [26], rehabilitation management of breast cancer survivors [27], virtual reality-based training for daily living in patients with chronic stroke [28], PSTD treatments [29], foreign language learning gamification using virtual reality [30,31], K-12 and higher education [15,17], surgical training [32], industrial skills training [31], virtual reality cognitive training in individuals with mild cognitive impairment [16,18], science education [33,34], sensorimotor learning [35], dental education [36], virtual reality-based emotional response and symptom provocation in patients with OCD (obsessive compulsive disorder) [37], nursing education [38,39], virtual reality therapy for social anxiety disorder [40], evacuation training [41], virtual reality-assisted neuromuscular therapy [42], home-based virtual reality rehabilitation for individuals with Parkinson disease [43], virtual realitybased physiology and anatomy learning [44], social work education [45], and marketing higher education …”
Section: Introductionmentioning
confidence: 99%